Applications of management science. Vol. 17 - Lawrence, Kenneth D.; Kleinman, Gary (Applications of management science., 2015)
The objective of this research annual is to present state-of-the-art studies in the application of management science to the solution of significant managerial decision making problems. We hope that this research annual will significantly aid in the dissemination of actual applications of management science in both the public and private sectors. Topics will include: applied management science studies in finance, management, operations, supply chain and productivity. Applications of management science is critical reading for those academics, researchers, and practitioners of management science to the solution of significant managerial decision making problems in both the public and the private sectors.